Projected changes in mineral soil carbon of European croplands and grasslands, 1990-2080 - Smith, J; Smith, P; Wattenbach, M; Zaehle, S; Hiederer, R; Jones, R.J.A; Montanarella, L; Rounsevell, M.D.A; Reginster, I; Ewert, F (Global change biology, 2005)
We present the most comprehensive pan‐European assessment of future changes in cropland and grassland soil organic carbon (SOC) stocks to date, using a dedicated process‐based SOC model and state‐of‐the‐art databases of soil, climate change, land‐use change and technology change. Soil carbon change was calculated using the Rothamsted carbon model on a European 10 × 10′ grid using climate data from four global climate models implementing four Intergovernmental Panel on Climate Change (IPCC) emissions scenarios (SRES). Changes in net primary production (NPP) were calculated by the Lund–Potsdam–Jena model. Land‐use change scenarios, interpreted from the narratives of the IPCC SRES story lines, were used to project changes in cropland and grassland areas. Projections for 1990–2080 are presented for mineral soil only. Climate effects (soil temperature and moisture) will tend to speed decomposition and cause soil carbon stocks to decrease, whereas increases in carbon input because of increasing NPP will slow the loss. Technological improvement may further increase carbon inputs to the soil. Changes in cropland and grassland areas will further affect the total soil carbon stock of European croplands and grasslands. While climate change will be a key driver of change in soil carbon over the 21st Century, changes in technology and land‐use change are estimated to have very significant effects. When incorporating all factors, cropland and grassland soils show a small increase in soil carbon on a per area basis under future climate (1–7 t C ha−1 for cropland and 3–6 t C ha−1 for grassland), but when the greatly decreasing area of cropland and grassland are accounted for, total European cropland stocks decline in all scenarios, and grassland stocks decline in all but one scenario. Different trends are seen in different regions. For Europe (the EU25 plus Norway and Switzerland), the cropland SOC stock decreases from 11 Pg in 1990 by 4–6 Pg (39–54%) by 2080, and the grassland SOC stock increases from 6 Pg in 1990 to 1.5 Pg (25%) under the B1 scenario, but decreases to 1–3 Pg (20–44%) under the other scenarios. Uncertainty associated with the land‐use and technology scenarios remains unquantified, but worst‐case quantified uncertainties are 22.5% for croplands and 16% for grasslands, equivalent to potential errors of 2.5 and 1 Pg SOC, respectively. This is equivalent to 42–63% of the predicted SOC stock change for croplands and 33–100% of the predicted SOC stock change for grasslands. Implications for accounting for SOC changes under the Kyoto Protocol are discussed.